Aspects Concerning the Use of the Moodle Platform – Case Study. (2015) - Gogan, Maria Luminita; Sirbu, Roxana; Draghici, Anca
Abstract: Exponential growth in computing over the past decade has triggered the development of many useful IT tools and implicit teaching, development of several E-learning platforms, which have become more familiar to teachers and students. Generic learning E-learning can be defined as distance learning in a progressive and collaborative learning, which combines traditional teaching methods with methods based on IT resources with the objective of increasing the performance of individual learners. Learning E-learning is based on modern teaching in a different way than classic which is more attractive and has an important role of knowledge building and evaluation performed in an attractive manner and custom, both those directing learning, especially as learners - pupils or students. This paper intends to present the functionalities of the E-learning platforms. This approach underlines identifying the training of students in using Moodle platform, based on a SWOT analysis and based on a questionnaire survey. The questionnaires were pooled using Google Docs platform. The results obtained from the questionnaires have shown some positive and some negative aspects.